Risk Factors for Glaucoma Drainage Device Exposure in a Middle-Eastern Population. Issue 6 (June 2019) - Al-Beishri, Ali S.; Malik, Rizwan; Freidi, Alia; Ahmad, Sameer
Abstract : Précis: In this case-control study, female sex, and older age were risk factors for tube exposure; risk was related to the number of prior ocular surgeries and scleral patch graft (compared with pericardial graft) was found to protect against exposure. Purpose: Identification of potential risk factors for glaucoma drainage device (GDD) exposure may help to prevent this potentially blinding complication. The purpose of this study was to evaluate the possible risk factors for GDD exposure in a tertiary eye care center in the Middle-East. Methods: A retrospective case-control study was undertaken for a 7-year period (2008 to 2015 inclusive). All patients who presented with a GDD incident exposure were identified and were compared with a similar number of controls (without exposure) identified during the same period. Demographic factors, past ocular history, treatment, and surgical technique were recorded for both groups. Bivariate and multivariable analyses were used to identify possible risk factors for tube exposure. Results: A total of 836 patients underwent GDD surgery during this time period and 53 patients were identified with exposure, giving a cumulative incident exposure rate of 6.3% (0.9% per year). Bivariate analysis showed that the median age of cases (51 years) was similar to controls (53 years) ( P =0.95), while there was a greater proportion of women with exposure (49%) compared with the control group (28%) with a statistically significant difference ( P =0.028). The number of previous surgeries (3.77±2.1) was significantly higher ( P =0.018) in the exposure group (4.25±2.0) compared with controls (3.3±2.0). With each unit increase in the number of previous surgeries, the odds of exposure significantly increased by 1.29 (95% confidence interval, 1.05-1.57). In the multivariable regression, female sex ( P =0.006) and older age ( P =0.025) were significant risk factors and use of a scleral patch ( P =0.02) graft potentially protective. Conclusions: Previous surgery, female sex, and older age are potential risk factors identified in our study. The use of scleral patch graft is potentially protective against GDD extrusion. Further study is needed to elucidate the reasons for these causative and protective factors.